BRAINSTORMING TO IMPROVE STUDENT CARING KNOWLEDGE - Putri, Prestasianita; Mardijanto, Said; Adelia Susanti, Ika (Abdi Dosen : Jurnal Pengabdian Pada Masyarakat, 2023)
Background: Caring is the essence of nursing. Caring requires refraction in its implementation. Caring for nursing students, as prospective professional nurses is considered lacking. Objective : Increase knowledge about caring for nursing students Methods: using brainstorming, which was done on 35 nursing students. Results: The implementation of the activity is by dividing 35 students into 4 groups, so that 1 group consists of 8-9 students. Each group received an explanation of the procedures for implementing brainstorming, working on the pre-then each group brainstorming on the topic of caring. Conclusion: After brainstorming with the topic of caring, it is hoped that students will increase student knowledge, and can do refraction with the support of friends (peer group support).